USING YOUTUBE NEWS AMID COVID-19 PANDEMIC AT SENIOR HIGH SCHOOL TO ENHANCE LISTENING AND WRITING SKILLS - Ahmad Zaini; Triyana (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2021)
It is common for English teachers in Senior High School to use YouTube to teach English especially in the time of the COVID-19 Pandemic. However, not many teachers share that practice in the form of publication, especially from regencies that quite far from the capital cities. This topic becomes interesting since it can be used in engaging students to be active in learning listening and writing. Nevertheless, teachers must consider several steps before applying this teaching practice. This article specifically explains about using YouTube News during COVID-19 as a pedagogical innovation for high school students in one of the government-owned schools in South Kalimantan to enhance their listening skills through watching the YouTube News and writing some comments about the news. The practical implication of the project is that the students can have a meaningful and memorable online activity to improve the students’ skill of English, especially listening and writing skills.